Safety and efficacy of carmustine (BCNU) wafers for metastatic brain tumors - Ene, Chibawanye I. (Surg Neurol Int, 2016)
BACKGROUND: Carmustine (BCNU) wafers (Gliadel) prolongs local disease control and progression-free survival (PFS) in patients with malignant gliomas. However, in metastatic brain tumors, there is a paucity of evidence in support of its safety and efficacy. The goal of this study was to assess the safety and efficacy of Gliadel wafers in patients with metastatic brain tumors. METHODS: We retrospectively reviewed the University of Washington experience with Gliadel wafers for metastatic brain tumors between 2000 and 2015. RESULTS: Gliadel wafers were used in 14 patients with metastatic brain tumors during the period reviewed. There were no postoperative seizures, strokes, or hemorrhages. There was one postoperative wound infection necessitating return to the operating room. The mean time to tumor progression (n = 7) and death (n = 5) after Gliadel wafer implantation was 2.5 and 2.9 years, respectively. Age was the only variable affecting PFS in patients receiving Gliadel wafers. Patients <53 years old (n = 7) had a PFS of 0.52 years, whereas patients >53 years old (n = 7) had a PFS of 4.29 years (P = 0.02). There was no significant difference in PFS in relation to presenting Karnofsky Performance Status (P = 0.26), number of brain metastasis (P = 0.82), tumor volume (P = 0.54), prior surgery (P = 0.57), or prior radiation (P = 0.41). There were no significant differences in the mean survival in relationship to any variable including age. CONCLUSIONS: BCNU wafers are a safe and a potentially efficacious adjunct to surgery and radiation for improving local disease control in metastatic brain tumors. Larger studies, however, are needed to examine overall efficacy and tumor specific efficacy.